ARAH PEMBANGUNAN DAN PEMBERDAYAAN DESA WATESUMPAK DIDASARKAN PADA KESESUAIAN RPJMDES TAHUN 2015-2020 - Al-Aziz Erya Putra, Sultan; Muhaimin, Hikmah; Suprapto (MAJAPAHIT POLICY, 2023)
This research discusses the implementation of the RPJMDES in the field of development and empowerment in DeesaWatesumpak, Trowulan District, Mojokerto Regency. There is a problem formulation, namely regarding the process of preparing the RPJMDES,factors inhibiting and supporting the implementation of the RPJMDES and the implementation of the RPJMDES in the field of development andempowerment. This research uses 2 theories, namely development and empowerment theory by Edi Suharto. Deep goalsThis research is to find out how the written RPJMDES conforms to the immediate conditions found in itfield and inhibiting and supporting factors in the realization of RPJMDES in Watesumpak village.The method used is a qualitative case study method. This data collection technique uses observation, interviews, anddocumentation. Based on the results of this research, it is revealed that First, the process of preparing the RPJMDes was formulated bycommunity in MUSDES, then deposited with BPD to be determined by SEKDES, village officials carry out alignmentvillage data or comparing Watesumpak Village data with current village conditions. Village Secretary. Second, the inhibiting factor is the budgetand unexpected conditions, and the supporting factor is community involvement in conveying aspirations and participationsociety in development. Third, implementation in the development sector, there are 9 programs that have been agreed upon and have been implementedThere are programs underway and there is 1 development program that has not been implemented, namely in every rainy season through normalizationflood control channels in every rainy season through normalization of village irrigation channels, and in the field of empowermentthere are 13 programs that have been mutually agreed upon, there are 12 programs that have been implemented and there is 1 program that has not been implementednamely in empowering the conservation of underground water sources